A banquet for Alphonse Lemerre, the poets’ publisher - St. Onge, Ruth-Ellen (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2011)
The Banquet offert à M. Alphonse Lemerre is a document associated with an event which took place at the Palais d’Orsay on the 24 January 1902 in order to celebrate the promotion of the publisher Lemerre to the rank of Officier in the Légion d’honneur. The document is printed with great care in order to display the taste and the art of the publishing house of Lemerre, known for its editions of contemporary poets (above all, the Parnassians), as well as the poets of the Pléiade. In addition, it reproduces the speeches and toasts given by Lemerre and his guests José-Maria de Heredia, André Theuriet and other poets. The analysis of the discourse proffered by Lemerre in his speech, as well as that of his guests, will help us to understand his role as publisher, which, under pressure by the opposition of symbolic and material values, became more and more contradictory as the century wore on. Above all, the article will show how the Banquet highlights the ambivalence at the heart of Lemerre’s posture as an artistic, honest and paternal publisher of poets.